Can foreign aid curb migration to the U.S. by creating a better alternative? - Hernandez, Manuel A.; Piñeiro, Valeria; Berrospi, Maria Lucia (International Food Policy Research Institute, 2025)
There are over 11 million undocumented immigrants living in the United States. More than half of this population is from Mexico (37%) and Central America (19%) (Figure 1). Over the past four years, annual apprehensions of foreign nationals at U.S. borders—most along the border with Mexico—have fluctuated between 1.6 million and 2.2 million. About two-thirds of these migrants are similarly from Mexico and Central America, particularly Guatemala, Honduras, Nicaragua, and El Salvador.